Peningkatan Kelarutan Glukomanan Porang (Amorphophallus muelleri Blume) dengan Penggilingan Basah dan Kering - Anny Yanuriati; Dasril Basir (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Despite of hydrophilic, glucomannan solubility is so slow that its solubility increase is required for easier, faster, and wider application. This research objective was to find a milling method which can enhance glucomannan solubility with high sol transparency, WHC and apparent viscosity. Native glucomannan extract from porang corm was classified into 3 treatments, no milling (native), grinding to pass through 80 mesh sieve (dry milling) or before grinding, the glucomannan were dissolved and precipitated using ethanol (wet milling) which then dried and passed through 80 mesh sieve. Compared to dry milling (13%), wet milling could significantly enhance higher glucomannan solubility (18%) with high sol transparency, WHC and apparent viscosity due to its depolymerization, molecular weight reduction, more porous and amorphous morphology as well.